2017
DOI: 10.1016/j.jcjd.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Distress and Depression in South Asian Canadians with Type 2 Diabetes

Abstract: This is the first study to report that diabetes distress is a serious concern for South Asian Canadians with type 2 diabetes. Given that depression and diabetes distress are linked, studies recruiting a larger and more diverse sample of South Asian Canadians should be conducted to better understand the psychological issues that may impact diabetes self-management in this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…The association of increased diabetes distress with poor glycaemic control corroborates findings by Cummings et al [ 5 ] and Hayashino et al [ 6 ] but is contrary to reports of no association between the variables [ 32 34 ]. When people with diabetes are distressed or experience depressive symptoms, their treatment regimen is likely to be affected and this can result in poor self-care and thus poor diabetes control.…”
Section: Discussionsupporting
confidence: 88%
“…The association of increased diabetes distress with poor glycaemic control corroborates findings by Cummings et al [ 5 ] and Hayashino et al [ 6 ] but is contrary to reports of no association between the variables [ 32 34 ]. When people with diabetes are distressed or experience depressive symptoms, their treatment regimen is likely to be affected and this can result in poor self-care and thus poor diabetes control.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have adopted an average DDS score of 2 as the cutoff point to evaluate the level of diabetes distress in Chinese patients with T2DM (Bao et al, 2018;Wang, 2017;Zhang et al, 2013). There is a close relationship between diabetes distress and depression (Sidhu & Tang, 2017;Zhang et al, 2013), and our data showed a significant correlation (r = 0.510, p < .001). Using the PHQ-9 results as criterion validity, we found the average DDS score of 1.93 showed the highest Youden's index of 0.415, with a sensitivity of 0.687 and specificity of 0.728, and the area under the receiver operating characteristic curve (AUC) was 0.782.…”
Section: Measurementssupporting
confidence: 49%
“…4 Sebanyak 52,5% pasien dengan diabetes melitus tipe 2 mengalami diabetes distress yang disertai dengan meningkatnya kadar HbA1c. 5 Hasil penelitian lain mengatakan 18,0% pasien diabetes melitus mengalami diabetes distress yang disertai dengan meningkatnya nilai HbA1c. 6 Penelitian di RSUD dr Soebandi Jember diperoleh data 93,3% pasien yang dirawat dengan diabetes melitus mengalami diabetes distress sedang dan sebagian besar pasien diabetes melitus tipe 2 mengatakan kalau mereka membutuhkan dukungan untuk perawatan dan manajemen diri yang bagus terhadap penyakitnya sehingga pasien mampu untuk mengontrol kadar gula darahnya.…”
Section: Diabetes Distressunclassified